Pengaruh Berbagai Komposisi Media Tanam Dan Varietas Terhadap Pertumbuhan Serta Hasil Tanaman Kentang (Solanum Tuberosum L.) Di Dataran Mediu Banyuresmi Garut - Almubarok, Abdul Fatah; Nurdiana, Dadi; Sativa, Novriza (Universitas Garut, 2025)
Potato (Solanum tuberosum L.) is one of the important horticultural commodities in Indonesia. Potato cultivation is usually carried out in highland areas however, continuous planting in these regions can cause environmental damage, such as land degradation. One solution is to reduce highland cultivation and explore alternative planting methods in mid-altitude areas using different planting media compositions to optimize growth. This study was conducted in Kp. Cikarokrok, Banyuresmi District, Garut Regency, West Java, from May to August 2024. The experimental site is located at an altitude of approximately 701 meters above sea level. The experiment employed an experimental method using a Split Plot Design with two factors: variety (main plot) consisting of v₁ = Medians variety and v₂ = AR 08 variety, and planting media composition (sub-plot) consisting of m₁ = 1:1:1:1, m₂ = 2:1:1:1, m₃ = 3:1:1:1, and m₄ = 4:1:1:1. The results showed no interaction between planting media composition and potato variety in terms of growth and yield. However, the independent effect of media composition m₁ (1:1:1:1) was significant on plant height, dry plant weight, the number of tubers per plant, and tuber weight per plant. Meanwhile, treatment m₂ (2:1:1:1) significantly affected plant height and the number of tubers per plant, while treatment m₃ (3:1:1:1) influenced plant height. The Medians variety exhibited better leaf area and dry plant weight compared to the AR 08 variety.